The Fulfillment of Young Couple Economics Needs for Family Welfare Improvement - Kadek Diah Dwijayanthi; Mutimmatul Faidah; Sri Handajani (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
This study aims to determine the fulfillment of the economic needs of young couples and to describe family welfare in the eyes of young couples. Young couples in this study were men and women who had married when they were under 19. This qualitative research uses interviews, observation, and documentation to collect data. Test the validity of the data using triangulation to get the actual data. The study results indicate that the fulfillment of the family economy carried out by young couples is to maximize their basic abilities by profession as traders, workshop employees, odd jobs, and others who get wages below the minimum wage. The role and support of parents also affect the economic fulfillment of young couples' families. Efforts to fulfill the economy carried out by young couples have yet to be able to achieve a prosperous family. This affects the view of family welfare for families of young couples. For young couples, family welfare is a condition where a family is financially sufficient and able to meet the needs of each family member.